Effect of stirring rate on the size of hydroxyapatite nanoparticles synthesized by a modified heat-treated precipitation method - Hernández-Silva Eduardo; Vázquez-Hernández Fabiola; Mendoza-Acevedo Salvador; Pérez-González Mario; Tomás-Velázquez Sergio; Rodríguez-Fragoso Patricia; Mendoza-Álvarez Julio; Luna-Arias Pedro Juan (Processing and Application of Ceramics, 2023)
Chemical synthesis is one of the most employed methods to obtain crystalline hydroxyapatite nanoparticles. It is feasible to vary the synthesis conditions and study their effects on nanoparticle structure. In this work, hydroxyapatite nanoparticles were synthesised by a modified heat-treated precipitation method and varying stirring rate of the solution during the nucleation process. The main goal was to reduce the particle size without affecting the crystallinity degree of the synthesized material what is important for several use cases, such as biomedical applications. The produced materials were characterized by X-ray diffraction, Fourier transformed infrared spectroscopy, μ-Raman spectroscopy, X-ray photoelectron spectroscopy, high-resolution transmission electron microscopy and scanning electron microscopy. The nanoparticle’s size decreased by increasing the stirring rate during the nucleation step, showing that the employed synthesis method is efficient for obtaining hydroxyapatite nanoparticles of variable sizes without affecting the crystallinity degree.